A Survey on Computer based Deception Detection Techniques - George, Sabu; Pai M.M, Manohara; M Pai, Radhika (International Journal of Engineering and Technology, 2018)
Deception detection plays a great role in the criminology field and it is a challenge for investigators and researchers for identifying real liar from normal behavior. There is different methods available based on brain, face, voice, etc. each has its own advantages and disadvantages.  Most of the lie detection methods are based on the variation of skin resistance, respiratory rate (breath rate), heart beat rate, etc. by the physical contact of some sensors or equipment fixed on the body of the subject. These types of deception detection methods are obtrusive.  In case of non-contact deception detection methods there are no sensor used on the body of the subject and the testing is done without the knowledge of the subject being tested. This paper gives a review on all these deception detection techniques.